Manajemen Keuangan Rumah Tangga Dalam Meningkatkan UMKM di Desa Majungan - Rohmaniyah Rohmaniyah; Rani Nur Fitrianti; Nurul Alfian; Achmarul Fajar; Siti Salama Amar; Nurul Lutfiah (Jurnal Manajemen Riset Inovasi, 2024)
Financial management must start from household management first because household financial management is already good, this will advance Micro, Small and Medium Enterprises (MSMEs) because society already has a basis for keeping financial records. The service aims to help and analyze and provides solutions to sources of business financing funds and provides new insights into accounting and digital financial technology that can be implemented into simple financial bookkeeping for households and MSMEs. Financial planning in the household can be done by identifying financial conditions (what assets we own and has the potential for great value in the future), determines desires, determines main desires. When determining your desires, you need to do three things, namely making all the desires you want to achieve now and in the future, what you want and what you need, writing down the funds needed and the time to achieve them. The next step is to determine the main desires. Practical financial management strategies that need to be implemented by MSME players are as follows: (1) administering receivables, (2) administering accounts payable, (3) administering inventory, which has a strategic role for both businesses operating in trade sector. (4) Cash administration, useful in providing information about the amount of cash coming in and cash going out.